2020
DOI: 10.2174/1874471012666190916112904
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant and Antioxidant Effects of Gentisic Acid in a 177Lu-Labelled Methionine-Containing Minigastrin Analogue

Abstract: Background: The radiolabelling of receptor-binding peptides for therapy is a challenge since the peptide itself is exposed (during labelling, storage and transport) to radiation-induced damage, directly or indirectly, in aqueous solution. Hence, the use of radiostabilizers seems to be mandatory, especially in peptide molecules that contain radiation-sensitive amino acids Objective: The aim of this study was to investigate the effect of two stabilizers, gentisic acid and methionine, to delve into how each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This difference cannot be substantiated by the non-specific sorption of unbound [ 177 Lu]Lu 3+ on the HPLC column [ 43 , 57 , 58 , 59 ] because, in this particular case, the values determined by the HPLC methods significantly exceed the values obtained by the TLC methods. This has also been observed in several other studies [ 45 , 46 ]. To confirm that this impurity is not a cationic form of 177 Lu or its weak associate with other possible ligands in the sample (such as acetate-anion), we conducted a comparative experiment using a CM cation-exchange cartridge (Sep-Pak Accell Plus CM Plus Light Cartridge (Milford, MA, USA)), which is often used for the final purification of radiopharmaceuticals with metal radionuclides in manual and automated synthesis.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This difference cannot be substantiated by the non-specific sorption of unbound [ 177 Lu]Lu 3+ on the HPLC column [ 43 , 57 , 58 , 59 ] because, in this particular case, the values determined by the HPLC methods significantly exceed the values obtained by the TLC methods. This has also been observed in several other studies [ 45 , 46 ]. To confirm that this impurity is not a cationic form of 177 Lu or its weak associate with other possible ligands in the sample (such as acetate-anion), we conducted a comparative experiment using a CM cation-exchange cartridge (Sep-Pak Accell Plus CM Plus Light Cartridge (Milford, MA, USA)), which is often used for the final purification of radiopharmaceuticals with metal radionuclides in manual and automated synthesis.…”
Section: Resultssupporting
confidence: 89%
“…Notably, the [ 177 Lu]Lu-PSMA-617 samples already obtained with gentisic acid during the first day after synthesis began to acquire a brown color (which became more saturated during further storage— Figure 15 C). This color change is most likely due to the formation of gentisic acid oxidation products (such as 1,4-benzoquinone-2-carboxylic acid and others [ 46 , 48 , 79 ]) upon interaction with radicals during radiolysis. The samples prepared with the mixture of cysteine and DMSA remained clear and colorless throughout the monitoring period (up to 144 h), and no eye-visible precipitate formation was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All [ 68 Ga]Ga-OncoFAP and [ 18 F]AlF-OncoFAP radio-conjugates were highly stable (>99% of intact compound) in 0.9% saline solution and in human plasma at 37 • C for 2 h. On the other hand, a stability test of [ 177 Lu]Lu-DOTAGA-OncoFAP radiolabeled batch showed the presence of radiolysis of about 10% every 24 h, which was significantly reduced to about 2% within 8 days by the addition of 20 mg of gentisic acid as a radical scavenger (Figure 3b) [15,16]. All the radiolabeled preparations of OncoFAP derivatives exhibited high hydrophilicity.…”
Section: Preliminary In Vitro/in Vivo Characterization Of Oncofa-deri...mentioning
confidence: 99%
“…Several studies have been reported related to the interactions of 2,5-dihydroxybenoic acid with other metal ions in addition to iron [146,147]. However, there are not as many reports on the iron-binding and metabolic effects of 2,5-dihydroxybenzoic acid in comparison to those of 2,3-DHB and salicylic acid.…”
Section: Interactions Of Salicylic Acid With Ironmentioning
confidence: 99%